2015
DOI: 10.1002/srin.201400305
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Titanium Compounds in Blast Furnace Hearth During Titania Addition

Abstract: The longevity of an iron making blast furnace is largely limited by the erosion of hearth refractory. The addition of titanium (Ti)‐bearing materials into the furnace may promote so‐called Ti‐rich scaffolds along the damaged hearth lining. A Computational Fluid Dynamics model is used to investigate the complex transport phenomena associated with the formation and dissolution of solid particles. Based on the modeling results, the isotherm of the equilibrium temperature of the incoming hot metal solution can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The BF hearth phenomena have been investigated mainly based on mathematical and experimental modeling because the in‐hearth variables cannot be directly measured during the continuous operation . As for the skulling behavior, Zhao et al were among the first to put dedicated efforts into simulating skull formation utilizing a two‐dimensional computational fluid dynamics (CFD) model .…”
mentioning
confidence: 99%
“…The BF hearth phenomena have been investigated mainly based on mathematical and experimental modeling because the in‐hearth variables cannot be directly measured during the continuous operation . As for the skulling behavior, Zhao et al were among the first to put dedicated efforts into simulating skull formation utilizing a two‐dimensional computational fluid dynamics (CFD) model .…”
mentioning
confidence: 99%
“…To be able to estimate the state of the hearth, some models for calculating the remaining sound lining and the amount of scaffold on the bottom and sidewall based on thermocouple readings has been developed. [10][11][12][13] For example, Keisuke et al 14) reported on the use of the scaffold thickness to monitor the hearth lining and to take control actions against erosion. But the information of the scaffold such as the thermal conductivity is hypothetical.…”
Section: Characterization and Properties Of Scaffold In A Dissected Bmentioning
confidence: 99%
“…Therefore, this model can predict the spatial distributions of volume fraction of Ti(C,N) particles, their sizes, and their melting‐forming boundary, as shown in Figure . This study was further conducted by Komiyama et al, who found that the isotherm of the equilibrium temperature of the hot metal can be used as an indicator for the extent and phase of Ti compounds, and on this basis, adjusted this isotherm to control the particle formation in the hearth by either altering the inlet titanium mass fraction or the hot metal pool temperature through systematic simulations. Recently, Zhao et al integrated the solidification model based on the melt/freeze enthalpy‐porosity technique into the flow and heat transfer models to describe the formation of skull.…”
Section: Modeling and Simulation Of Different Bf Regionsmentioning
confidence: 99%
“…Ueda et al [12] in 2010 and Ariyama et al [13] in 2014 further discussed the new efforts reported for the discrete simulation of BF, respectively. However, the previous reviews did not pay much attention to the modeling efforts dedicated to hearth [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] and raceway, [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] of which the performance plays a critical role in determining BF campaign life, as well as operation and maintenance costs. Also, considerable model developments based on either discrete or continuum approach have been made recently.…”
mentioning
confidence: 99%